MG-145 Importance of fetal fraction analysis for CFDNA testing in the general pregnancy population. (4th December 2015) - Wang, Eric; Struble, Craig; Kingsley, Christopher; Steeke, Rhoberta; Batey, Annette; Hollemon, Desiree; Oliphant, Arnold; Musci, Thomas
Abstract : Background: Harmony™ Prenatal Test uses an assay method, Digital Analysis of Selected Regions (DANSR™), for analysis of chromosomes 13, 18, 21, X and Y as well as other chromosomes to measure fetal fraction (FF). Products from the DANSR assay are then analysed with Fetal fraction Optimised Risk of Trisomy Evaluation (FORTE™) algorithm to assess patient-specific risk of trisomy. Alternative tests, such as those using massively parallel shotgun sequencing, use a Z-statistic or Normalised Chromosome Value (NCV) to discriminate between normal and abnormal chromosomal counts without accounting for FF. Methods: A general pregnancy population cohort of 15, 841 women between 10.0 to 14.3 weeks gestation were followed to pregnancy outcome. Z-statistics were computed using previously described standard Z-test of proportions and compared to FORTE risk scores generated by Harmony. A Z-statistic of ≥3 was 'Positive' for trisomy and a FORTE risk score of ≥1% was 'High Risk' for trisomy. Results: See Table 1 . Cumulative test discordant rate for non-trisomies with FORTE was 0.08% compared to 1.07% with Z-statistic. Conclusion: Analysis using FORTE to incorporate FF in cfDNA testing yields >10 fold reduction in discordant results This will become increasingly relevant as cfDNA testing gets more broadly used in the general pregnancy population.